Liquid Silicone-Induced Extensive and Debilitating Granulomatosis Responding to Hydroxychloroquine - Nargis Jilani; Javeria Shabbir; Elena Nemytova (Case Reports in Rheumatology)
In the last two decades, there has been a significant rise in body-image improvement among the American consumers. Cosmetic injectable procedures have increased by 40.6% in the past 5 years. There has also been an increase in nonmedical, illegal, and self-appointed personnel, offering cheaper hazardous procedures. Silicone has been in use since 1965. In 1991, FDA issued guidelines prohibiting the marketing of injectable liquid silicone. However, it is biologically inert, is associated with inflammatory response, and leads to serious complications like granulomatosis, migration, acute pneumonitis, pulmonary embolism, and even death. Here, we present a case of silicone-induced granulomatosis with extensive migration which ended in bilateral mastectomy, multiple anterior chest debulking procedures, and finally peg tube placement due to compression of the esophageal lumen by granulomas. The patient was eventually started on immunomodulatory treatment, hydroxychloroquine with good response.